Interplay Between Mitophagy and Apoptosis Defines a Cell Fate Upon Co-treatment of Breast Cancer Cells With a Recombinant Fragment of Human κ-Casein and Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand - Wohlfromm, Fabian; Richter, Max; Otrin, Lado; Seyrek, Kamil; Vidaković-Koch, Tanja; Kuligina, Elena; Richter, Vladimir; Koval, Olga; Lavrik, Inna N. (Frontiers in Cell and Developmental Biology, 2021)
A recombinant fragment of human κ-Casein, termed RL2, induces cell death of breast cancer cells, however molecular mechanisms of RL2-mediated cell death have remained largely unknown. In the current study, we have decoded the molecular mechanism of the RL2-mediated cell death and found that RL2 acts via induction of mitophagy. This was monitored by the loss of ATP production, LC3B-II generation and upregulation of BNIP3, BNIP3L/NIX as well as PINK1. Moreover, we have analysed the cross-talk of this pathway with TRAIL-induced apoptosis upon combinatorial treatment with RL2 and TRAIL. Strikingly, we found two opposite effects of this co-treatment. RL2 had inhibitory effects on TRAIL-induced cell death upon short-term co-stimulation. In particular, RL2 treatment blocked TRAIL-mediated caspase activation, cell viability loss and apoptosis, which was mediated via the downregulation of the core pro-apoptotic regulators. Contrary to short-term co-treatment, upon long-term co-stimulation, RL2 sensitized the cells towards TRAIL-induced cell death, the latter observation provides the basis for the development of therapeutic approaches in breast cancer cells. Collectively, our findings have important implications for cancer therapy and reveal the molecular switches of the cross-talk between RL2-induced mitophagy and TRAIL-mediated apoptosis.